RETRACTED: Linguocultural study of anthroponyms in irrelative languages (on the material of English and Uzbek epics) - Vakhobova Feruza; Musayeva Nozima; Madaminova Sabina Alisher qizi; Bakhronova Mahliyo; Ziyadulloyeva Mohidil Shovkat qizi; Yuldashova Nargiza Abduxoliq qizi; Ergasheva Sarvinoz (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001